CYP2C19 genotypes and osteoporotic fractures in long‐term users of proton pump inhibitors: A hospital‐based study - Yi‐Ju Liao; Yu‐Ting Chen; Tzu‐Hung Hsiao; Ching‐Heng Lin; Ming‐Fen Wu; Chiann‐Yi Hsu; Yi‐Ming Chen; Chun‐Sheng Hsu (Wiley, 2023)
Abstract Proton pump inhibitors (PPIs) are commonly prescribed medications. The existing data suggest that individuals at a high risk of fractures have been exposed to high doses of PPIs for prolonged durations. CYP2C19 plays a pivotal role in metabolism of PPIs and thereby influences their pharmacokinetic profile. Hence, we hypothesize that CYP2C19 genotypes may be associated with fragility fracture among PPIs users due to PPI exposure. This study aimed to investigate the association between CYP2C19 genotypes, bone mineral density (BMD), and osteoporotic fracture in a hospital‐based population. This retrospective cohort study enrolled patients who were prescribed long‐term PPIs at Taichung Veterans General Hospital using data extracted from the Taiwan Precision Medicine Initiative between January 2010 and April 2021. Associations between CYP2C19 phenotypes, comorbidities, and fractures in PPI users were analyzed. We enrolled 1518 long‐term PPI users; 571 (38%), 727 (48%), and 220 (14%) CYP2C19 normal metabolizers (NMs), intermediate metabolizers (IMs), and poor metabolizers (PMs), respectively. Among them, 49 (3.2%) patients developed fractures within the 1‐year follow‐up period; 20 (3.5%) fractures in NMs, 24 (3.3%) in IMs, and 5 (2.3%) in PMs, respectively. No significant difference was observed among CYP2C19 genotypes and fracture. Additionally, BMD measurements during the 1‐year follow‐up period were made available among 75 participants. No significant difference in BMD between CYP2C19 PMs and non‐PMs was found. This real‐world, hospital‐based study concludes that CYP2C19 PMs/IMs are not associated with an increased risk for fractures or reduced BMD in individuals on long‐term PPI therapy.